1999
DOI: 10.1088/0954-0083/11/3/306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Aromatic Polyamides Containing 5-(4-Acetoxybenzoylamino) Side Groups

Abstract: New aromatic polyamides containing 5-(4-acetoxybenzoylamino) side groups have been synthesized by low-temperature solution polycondensation reaction of equimolar amounts of aromatic diamines having ether bridges with 5-(4-acetoxybenzoylamino)isophthaloyl chloride, in N -methylpyrrolidinone (NMP) as a solvent and in the presence of pyridine as acid acceptor. These polyamides were characterized by IR spectra, viscometry, differential scanning calorimetry (DSC), thermogravimetric analyses and dielectric measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The introduction of flexible aryl‐ether linkages in the polymer backbone is a frequently used approach, which imparts characteristics such as better solubility, melt processing, and improved toughness as compared with polymers without these flexible linkages . Also, it was found that the introduction of hexafluoroisopropylidene groups into the polymeric structure resulted in overall benefits for the polymer solubility, thermal, and environmental stability and electrical and dielectric performances, mainly attributed to the increase in free volume, small dipole, and low polarizability of the C–F bond .…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of flexible aryl‐ether linkages in the polymer backbone is a frequently used approach, which imparts characteristics such as better solubility, melt processing, and improved toughness as compared with polymers without these flexible linkages . Also, it was found that the introduction of hexafluoroisopropylidene groups into the polymeric structure resulted in overall benefits for the polymer solubility, thermal, and environmental stability and electrical and dielectric performances, mainly attributed to the increase in free volume, small dipole, and low polarizability of the C–F bond .…”
Section: Introductionmentioning
confidence: 99%
“…The polyamides containing acetoxybenzamide groups in the side chain were obtained by low temperature solution polycondensation reaction of equimolar amounts of 5-(4-acetoxybenzamido) isophthaloyl chloride, 4) with various aromatic diamines containing ether linkages, 44) in N-methylpyrrolidinone (NMP) as a solvent and in the presence of pyridine as acid acceptor, as previously reported [8,9]. These polymers have the structure 444, as shown in scheme 1.…”
Section: 789 59mentioning
confidence: 93%
“…The polyamides containing acetoxybenzamide groups in the side chain were obtained by low temperature solution polycondensation reaction of equimolar amounts of 5-(4-acetoxybenzamido) isophthaloyl chloride, I, with various aromatic diamines containing ether linkages, preformed 1,3,4-oxadiazole ring or hexafluoroisopropylidene units II, in N-methylpyrrolidinone (NMP) as a solvent and in the presence of pyridine as acid acceptor, as previously reported [4][5][6]. These polymers have the structure III, as shown in Scheme 1.…”
Section: Synthesis Of the Polymersmentioning
confidence: 99%
“…In this away it is possible to obtain good solubility without sacrifying the thermal and mechanical properties to a great extent [2,3]. The introduction of pendent acetoxybenzamide units in the macromolecular chain of polyamides improves the solubility while maintaining a fairly good thermal stability [4][5][6]. We took into account that the study of physical properties of such polymers in connection with conformational parameters of the macromolecular chain is of interest for future advanced applications.…”
Section: Introductionmentioning
confidence: 99%